(untitled) (Journal of Economic Additions, 2025)
Through this study, we aim to emphasize the importance of localizing Islamic environmental financing products to support and promote ecotourism in Algeria. The ecotourism sector represents a strategic alternative for sustainable development, given the country’s rich natural and cultural resources that qualify it as a distinguished destination. Yet, this sector faces challenges, notably the limited traditional financing formulas and the lack of flexible mechanisms that balance profitability with social responsibility. Our study seeks to address this by examining Islamic financial products introduced to the Algerian market since 2008, highlighting their diverse financing efficiency and potential to meet various needs, including those of the ecotourism industry. Jel Classification Codes : Q50 ، Z32، Z33.